On the semantics of 'wh'- - Ruys, Eddy G. (Proceedings of Sinn und Bedeutung, 2023)
It is argued that a theory of the semantics of 'wh'-expressions, and 'wh'-pro-forms in particular, should not only fit the semantics of 'wh'-interrogatives. It should also provide a simple and unified cross categorial semantics for 'wh'- which takes into account the semantics of morphologically and cross-linguistically plausible paradigm-mates, while deriving rather than stipulating the correct types for traces/variables, and allowing 'in-situ' interpretation. Accordingly, it is proposed that 'wh'-pro-forms are variants of demonstratives, with 'wh'- a proximity value next to PROXIMAL or DISTAL (or rather: their unvalued counterpart). The familiar phenomenon of deferred reference with demonstratives is taken to underlie the crosscategorial semantics of demonstratives, hence that of 'wh'-expressions as well. 'Wh'-expressions end up functioning as unselectively bound, presuppositionally restricted variables.